The Relationship Between Knowledge And Smoking Habits On The Incidence Of Hypertension At The Bukit Sari Health Center, Kepahiang Regency - Amorita, Yulia; Syafrie, Ice Rakizah; Handayani, Tita Septi (Universitas Dehasen Bengkulu, 2024)
Based on data from the World Health Organization (WHO) for the 2015-2020 period, it shows that around 1.13 billion individuals worldwide have hypertension. According to Riskesdas data released by the Indonesian Ministry of Health in 2021, the prevalence of hypertension in Indonesia reached 34.1%. Data from the Kepahyang Regency Health Office in 2020 amounted to 22,188 cases with a prevalence of 28.1%. The purpose of this study was to determine the relationship between knowledge and smoking habits on the incidence of hypertension at the Bukit Sari Health Center, Kepahiang Regency in 2024.The type of research used in this study is analytical observational, data collected by distributing questionnaires to 75 respondents at the Bukit Sari Health Center, Kepahiang Regency.The results of the univariate test analysis showed that more than half of the respondents 41 (54.7%) had poor knowledge, almost half of the respondents 36 (48%) had current smoking habits and more than half of the respondents 51 (68%) had hypertension. The results of the bivariate analysis showed that there was a relationship between knowledge and the incidence of hypertension at the Bukit Sari Health Center, Kepahiang Regency in 2024 with a p value of 0.006 and there was a relationship between smoking habits and the incidence of hypertension at the Bukit Sari Health Center, Kepahiang Regency in 2024 with a p value of 0.001.The researcher suggests providing a better understanding of the impact of knowledge and smoking habits on their health conditions, especially hypertension. By knowing the relationship between smoking and hypertension, respondents can be more aware of the importance of increasing health knowledge and changing smoking habits to manage and prevent hypertension.